(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Researchers have often emphasized the significance of motivation, attitude and self- confidence in learning English as a second or foreign language. Motivation has been considered as one of the most important factors that affect the process of learning English as a second language. It is the motivation which gives the required impetus for pursuing an action towards achieving a particular goal despite several impediments. Today, the advancements in science and technology have created umpteen job and business opportunities to people who are able to meet the requirements of the industry. This single factor enticed students to pursue engineering education in India.An engineering graduate besides having knowledge in his or her specific domain should possess required communication skills to excel in the world of opportunities as suggested by several committees. Hence, it is essential to understand motivation for learning English among the engineering students, so that they can be motivated to learn English by facilitating them with the required inputs which can meet their needs.The main aim of this study is to identify the motivation (Instrumental or Integrative) for learning English among students pursuing their Engineering education in Vijayawada.